Exploring Consumer Credit Impact on Debtor Welfare at Bank Branch Office - Kapisa, Ronald Zeth; Situmorang, Elina Relawaty; Werimon, Simson (Research Horizon, 2025)
Household consumption represents a key driver of regional economic growth, as it influences aggregate demand and contributes substantially to gross regional domestic product. Access to consumer credit offered by financial institutions enables households to maintain consumption stability and fulfill essential needs, potentially enhancing welfare. However, if mismanaged, credit may result in excessive financial burdens and reduced quality of life. This study aims to examine the effect of consumer credit on debtor welfare. A quantitative approach was applied using a simple linear regression analysis, with data collected through questionnaires distributed to consumer credit debtors. The results indicate a statistically significant positive effect of consumer credit on debtor welfare, as shown by a regression coefficient of 0.587 and a significance value below 0.05. These findings suggest that increased access to credit contributes to improved household welfare. The study highlights the importance of strengthening credit service quality and promoting responsible financial behavior to ensure that consumer credit functions as a tool for improving welfare rather than creating financial distress. Insights from this research can support banks and local governments in formulating policies that enhance financial inclusion and sustainable economic well-being.